Exclusion of Glochidion coccineum (Phyllanthaceae) from the flora of China - Yao, Gang; Song, Zhuqiu; Li, Yuling; Shi, Shi; Luo, Shixiao (Phytotaxa, 2019)
The species Glochidion coccineum has long been considered to be widely distributed in China. Based on results from extensive specimen examinations and field investigations, we demonstrate that all the Chinese specimens previously identified as G. coccineum belong to G. daltonii, G. ellipticum, G. lanceolarium, G. oblatum, G. puber or G. sphaerogynum. Glochidion coccineum is not known to China and thus the distribution of the species in China is excluded. Filed images as well as a key to G. coccineum and relevant misidentified species are provided.